Effect of a twin-herb formula for the Treatment of Chronic Non-healing Ulcers: a Clinical Study - Ping-Chung LEUNG; Tommy Nai- Ming LUK; Heidi CORCORAN; Chun -Hay KO; Leung-Kim HUNG; Lung- Fung TSE; Hi-shan CHENG; Winnie W.M. LO; Ellie S.Y. PANG; King-Fai CHENG (Open Journal of Plant Science - Peertechz Publications, 2017)
Forty-four patients (27 males and 17 females) with Chronic Non-healing Ulcers that had been refractory to conventional treatment were enrolled in a single arm pre- and post-treatment clinical trial. A twin-herb formula was provided for the treatment for the 6-month study period. All conventional treatment of wound care remained unchanged. Their ulcers were assessed every month. The ulcer sizes greatest length and width was measured at baseline. The target ulcer was assessed at baseline and then every month for 6 months or healed. The mean age of patients was 66.6 (38.0-93.0) years. The mean surface area of ulcers was 28.0±77.1 cm2 and 14.8±55.0 cm2 at baseline and six months of study respectively. Differences in ulcer area between the initial and fi nal visit were signifi cant (p<0.001). The mean healing time was 149 days (median 167 days). Our results showed that the two-herb recipe (NF3) could reduce the wound size about 50% during 6 months period. 36.7% ulcers were healed. No adverse side effects were founded in our patients during study period. The twin-herb formula showed promising results in initiating the healing process in chronic nonhealing ulcers. It was found to be well tolerated and safe to use. However, further clinical trials should be performed involving a control group to verify these data.